The Relative Contribution of Symptomatic and Asymptomatic Plasmodium vivax and Plasmodium falciparum Infections to the Infectious Reservoir in a Low-Endemic Setting in Ethiopia. (3rd January 2018) - Tadesse, Fitsum G; Slater, Hannah C; Chali, Wakweya; Teelen, Karina; Lanke, Kjerstin; Belachew, Mulualem; Menberu, Temesgen; Shumie, Girma; Shitaye, Getasew; Okell, Lucy C; Graumans, Wouter; van Gemert, Geert-Jan; et al.
Abstract : Microscopically detectable asymptomatic Plasmodium vivax and Plasmodium falciparum infections form the most important source of onward mosquito infections in a low-endemic setting in Ethiopia. Plasmodium vivax symptomatic infections are highly infectious but less prevalent and thereby contribute less to transmission. Abstract: Background: The majority of Plasmodium vivax and Plasmodium falciparum infections in low-endemic settings are asymptomatic. The relative contribution to the infectious reservoir of these infections compared to clinical malaria cases is currently unknown. Methods: We assessed infectivity of passively recruited symptomatic malaria patients (n = 41) and community-recruited asymptomatic individuals with microscopy-detected (n = 41) and polymerase chain reaction (PCR)–detected infections (n = 82) using membrane feeding assays with Anopheles arabiensis mosquitoes in Adama, Ethiopia. Malaria incidence and prevalence data were used to estimate the contributions of these populations to the infectious reservoir. Results: Overall, 34.9% (29/83) of P. vivax– and 15.1% (8/53) P. falciparum– infected individuals infected ≥1 mosquitoes. Mosquito infection rates were strongly correlated with asexual parasite density for P. vivax (ρ = 0.63; P < .001) but not for P. falciparum (ρ = 0.06; P = .770) . Plasmodium vivax symptomatic infections were more infectious to mosquitoes (infecting 46.5% of mosquitoes, 307/660) compared to asymptomatic microscopy-detected (infecting 12.0% of mosquitoes, 80/667; P = .005) and PCR-detected infections (infecting 0.8% of mosquitoes, 6/744; P < .001). Adjusting for population prevalence, symptomatic, asymptomatic microscopy-detected, and PCR-detected infections were responsible for 8.0%, 76.2%, and 15.8% of the infectious reservoir for P. vivax, respectively. For P. falciparum, mosquito infections were sparser and also predominantly from asymptomatic infections. Conclusions: In this low-endemic setting aiming for malaria elimination, asymptomatic infections were highly prevalent and responsible for the majority of onward mosquito infections. The early identification and treatment of asymptomatic infections might accelerate elimination efforts.